Mechanisms Involved in the Association between Periodontitis and Complications in Pregnancy - Zi, Marcela Yang Hui; Longo, Priscila Larcher; Bueno-Silva, Bruno; Mayer, Marcia Pinto Alves (Frontiers in Public Health, 2015)
The association between periodontitis and gestation complications such as premature delivery, low weight at birth and preeclampsia has been suggested. Nevertheless, epidemiological data have shown contradictory data, mainly due to differences in clinical parameters of periodontitis assessment. Furthermore, differences in microbial composition and immune response between aggressive and chronic periodontitis are not addressed by these epidemiological studies. We aimed to review the current data on the association between gestation complications and periodontitis, and the mechanisms underlying this association. Shifts in the microbial composition of the subgingival biofilm may occur during pregnancy, leading to a potentially more hazardous microbial community. Pregnancy is characterized by physiological immune tolerance. However, the infection leads to a shift in maternal immune response to a pathogenic pro-inflammatory response, with production of inflammatory cytokines and toxic products. In women with periodontitis, the infected periodontal tissues may act as reservoirs of bacteria and their products which can disseminate to the fetus-placenta unit. In severe periodontitis patients, the infection agents and their products are able to activate inflammatory signaling pathways locally and in extra-oral sites, including the placenta-fetal unit, which may not only induce preterm labor, but also lead to preeclampsia and restrict intrauterine growth. Despite these evidences, the effectiveness of periodontal treatment in preventing gestational complications was still not established since it may be influenced by several factors such as severity of disease, composition of microbial community, treatment strategy, and period of treatment throughout pregnancy. This lack of scientific evidence does not exclude the need to control infection and inflammation in periodontitis patients during pregnancy, and treatment protocols should be validated.